Impactful research fronts in digital educational ecosystem: advancing Clarivate’s approach with a new impact factor metric - Tran Ai Cam; Nguyen Huu Thanh Chung; Nguyen Huu Thanh Chung (Frontiers in Education)
IntroductionThis study explores impactful research fronts within the digital educational ecosystem using an extended Clarivate approach with a newly formulated Impact Factor (IF) metric. The research addresses limitations of the original Clarivate Citation Production Trajectory (CPT) by integrating a broader IF metric.MethodsThe IF metric expands evaluation by incorporating publication count, growth rate, core paper presence, and citation behavior. It also measures the publication gap between core and citing articles to track developmental shifts. Scopus data from 2019–2023 serve as the analysis base.ResultsThe analysis reveals key research fronts such as online learning, artificial intelligence, virtual reality, hybrid learning, and digital assessment. Online learning and AI emerge as the most influential.DiscussionThe IF metric enhances precision in detecting impactful fronts over CPT and maps global research activities, highlighting growing contributions from developing regions. This refined approach helps assess both short-term relevance and long-term influence in digital education. The findings emphasize a more inclusive landscape of impactful research across institutions and nations.